Determination of thermal properties of cryo- ground cinnamon powder - A Sharma, T J Zachariah, P Barnwal, K K Singh, A Mohite, (Journal of Spices and Aromatic Crops, 2014)
In this study, thermal properties, viz., specific heat, thermal conductivity and thermal diffusivity, of cryo- ground cinnamon powder (var. Navasree) were investigated. Cinnamon samples were ground using a cryogenic grinder at low temperature (generally below -50°C) using liquid nitrogen (LN2), having a grinder speed of 12000 rpm and 1 kg h-1 feed rate. The specific heat varied from 46.60-58.04 kJ kg-1°C within the temperature and moisture ranges of -100 - 100°C and 6.4-19.0% dry basis, respectively. Thermal conductivity and thermal diffusivity varied from 0.055 to 0.884 W m-1°C and 0.35 × 10-8 - 7.23 × 10-8 m2 s-1, respectively in the temperature and moisture ranges of -40-60°C and 6.4-19.0% db. The specific heat, thermal conductivity and thermal diffusivity showed quadratic relationships with temperature and moisture content and were significantly affected by moisture and temperature at 5% level of significance.